(untitled) (Universal International Scientific Journal, 2026)
The article analyzes the linguocultural characteristics of phraseological units with the “money” component in English and Uzbek. The concept of money reflects a person’s attitude to material and spiritual values ​​in both languages. The study highlights the semantic structure of phraseological units, their cultural foundations, their expression in national thinking, and problems in the translation process. Based on the linguocultural approach, phraseologisms are interpreted not only as a product of language, but also as a product of cultural thinking.